Metabolome and RNA-seq Analysis of Responses to Nitrogen Deprivation and Resupply in Tea Plant (Camellia sinensis) Roots - Xu, Wenluan; Li, Jing; Zhang, Luyu; Zhang, Xuyang; Zhao, Hua; Guo, Fei; Wang, Yu; Wang, Pu; Chen, Yuqiong; Ni, Dejiang; Wang, Mingle (Frontiers in Plant Science, 2022)
Nitrogen (N) is an important contributor in regulating plant growth and development as well as secondary metabolites synthesis, so as to promote the formation of tea quality and flavor. Theanine, polyphenols, and caffeine are important secondary metabolites in tea plant. In this study, the responses of Camellia sinensis roots to N deprivation and resupply were investigated by metabolome and RNA-seq analysis. N deficiency induced content increase for most amino acids (AAs) and reduction for the remaining AAs, polyphenols, and caffeine. After N recovery, the decreased AAs and polyphenols showed a varying degree of recovery in content, but caffeine did not. Meanwhile, theanine increased in content, but its related synthetic genes were down-regulated, probably due to coordination of the whole N starvation regulatory network. Flavonoids-related pathways were relatively active following N stress according to KEGG enrichment analysis. Gene co-expression analysis revealed TCS2, AMT1;1, TAT2, TS, and GOGAT as key genes, and TFs like MYB, bHLH, and NAC were also actively involved in N stress responses in C. sinensis roots. These findings facilitate the understanding of the molecular mechanism of N regulation in tea roots and provide genetic reference for improving N use efficiency in tea plant.